Раскопки кургана покровской срубной культуры у пгт Кировское в Нижнем Присамарье - Ромашко, В.А.; Фещенко, Е.Л. (Археологічні дослідження в Україні, 2009)
The paper presents the results of excavations at the mound in the Samara River lower region. The Late Bronze Age burials discovered there widen the circle of a few monuments of Pokrovska Zrubna culture in Steppe Zone of Ukraine.